Pendekatan Konseling Motivational Interviewing Dengan Teknik OARS Terhadap Perubahan Perilaku Maladaptif Peserta Didik - Mutia Adella; Yenti Arsini; Junita Hanum Eka Putri (Universitas Maritim AMNI Semarang, 2024)
This research is a literature analysis that aims to describe and investigate the concept, application and impact of the Motivational Interviewing (MI) approach with the OARS (Open-ended questions, Affirmations, Reflective listening. Summarizing) technique in various clinical contexts, especially on changes in participants' maladaptive behavior. students, such as aggressive behavior, unwillingness to learn, or non-compliance with school rules, can have a negative impact on students' academic and social progress. MI with OARS techniques has been used effectively in various clinical and educational contexts, but its role in changing students' maladaptive behavior still needs to be better understood. The research method used is literature study and descriptive analysis. This research collected data from various literature sources, including scientific journals, books, clinical guidelines, and published research reports. The results of the literature analysis show that MI with the OARS technique is a client-based approach that emphasizes collaboration, empathy, and encouragement for change. The MI concept includes building a strong therapeutic relationship, recognizing the client's independence, and increasing motivation for change.